2010
DOI: 10.1152/jn.01048.2009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Linear Coupling Between Single-Event Blood Flow Responses and Interictal Discharges in a Model of Experimental Epilepsy

Abstract: Vanzetta I, Flynn C, Ivanov AI, Bernard C, Bénar CG. Investigation of linear coupling between single-event blood flow responses and interictal discharges in a model of experimental epilepsy. J Neurophysiol 103: 3139 -3152, 2010. First published March 24, 2010 doi:10.1152/jn.01048.2009. A successful outcome of epilepsy neurosurgery relies on an accurate delineation of the epileptogenic region to be resected. Functional magnetic resonance imaging (fMRI) would allow doing this noninvasively at high spatial resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
(57 reference statements)
3
18
0
Order By: Relevance
“…3A). As we previously reported (Vanzetta et al 2010), we observed a 2-s delay between the ED events and the maximal amplitude of blood flow perfusion. Furthermore, the tissue oxygen response was delayed by 2.5 s; however, a 750-ms delay is to be expected from the time response of the oxygen probe (Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…3A). As we previously reported (Vanzetta et al 2010), we observed a 2-s delay between the ED events and the maximal amplitude of blood flow perfusion. Furthermore, the tissue oxygen response was delayed by 2.5 s; however, a 750-ms delay is to be expected from the time response of the oxygen probe (Fig.…”
Section: Resultssupporting
confidence: 86%
“…The amplitude of EDs was a good predictor of both CBF amplitude, confirming our previous work (Vanzetta et al 2010), and the oxygen response. Importantly, the baseline level of neuronal activity, as quantified by the inter-ED interval, was also an excellent predictor of both CBF and PO 2 amplitude fluctuations.…”
Section: Parametric Analysis Of Hemodynamic/metabolic Responsessupporting
confidence: 89%
See 3 more Smart Citations